Combined Regulatory T-Lymphocyte and IL-2 Treatment Is Safe, Tolerable, and Biologically Active for 1 Year in Persons With Amyotrophic Lateral Sclerosis. Issue 6 (29th November 2022) - Thonhoff, Jason R.; Berry, James D.; Macklin, Eric A.; Beers, David R.; Mendoza, Patricia A.; Zhao, Weihua; Thome, Aaron D.; Triolo, Fabio; Moon, James J.; Paganoni, Sabrina; Cudkowicz, Merit; Appel, Stanley H.
Abstract : Background and Objectives: In a phase 1 amyotrophic lateral sclerosis (ALS) study, autologous infusions of expanded regulatory T-lymphocytes (Tregs) combined with subcutaneous interleukin (IL)-2 were safe and well tolerated. Treg suppressive function increased and disease progression stabilized during the study. The present study was conducted to confirm the reliability of these results. Methods: Participants with ALS underwent leukapheresis, and their Tregs were isolated and expanded in a current Good Manufacturing Practice facility. Seven participants were randomly assigned in a 1:1 ratio to receive Treg infusions (1 × 10 6 cells/kg) IV every 4 weeks and IL-2 (2 × 10 5 IU/m 2 ) injections 3 times/wk or matching placebo in a 24-week randomized controlled trial (RCT). Six participants proceeded into a 24-week dose-escalation open-label extension (OLE). Two additional participants entered directly into the OLE. The OLE included dose escalation of Treg infusions to 2 × 10 6 cells/kg and 3 × 10 6 cells/kg at 4-week intervals. Results: The Treg/IL-2 treatments were safe and well tolerated, and Treg suppressive function was higher in the active group of the RCT. A meaningful evaluation of progression rates in the RCT between the placebo and active groups was not possible due to the limited number of enrolled participants aggravated by the COVID-19 pandemic. In the 24-week OLE, the Treg/IL-2 treatments were also safe and well tolerated in 8 participants who completed the escalating doses. Treg suppressive function and numbers were increased compared with baseline. Six of 8 participants changed by an average of −2.7 points per the ALS Functional Rating Scale–Revised, whereas the other 2 changed by an average of −10.5 points. Elevated levels of 2 markers of peripheral inflammation (IL-17C and IL-17F) and 2 markers of oxidative stress (oxidized low-density lipoprotein receptor 1 and oxidized LDL) were present in the 2 rapidly progressing participants but not in the slower progressing group. Discussion: Treg/IL-2 treatments were safe and well tolerated in the RCT and OLE with higher Treg suppressive function. During the OLE, 6 of 8 participants showed slow to no progression. The 2 of 8 rapid progressors had elevated markers of oxidative stress and inflammation, which may help delineate responsiveness to therapy. Whether Treg/IL-2 treatments can slow disease progression requires a larger clinical study (ClinicalTrials.gov number, NCT04055623). Classification of Evidence: This study provides Class IV evidence that Treg infusions and IL-2 injections are safe and effective for patients with ALS.